Mrs. Copley Amory autograph collection - Amory, Copley, Mrs.
Autograph collection.
Autograph collector.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Autographs -- Collections; Collectors, Autograph